Analysis of Clean Water Demand and Availability in Prambon Village using F.J Mock Method and Direct Testing in Tugu District, Trenggalek Regency - Wieke Pramesthy Artha Amalia; Vita Ayu Kusuma Dewi (G-Tech: Jurnal Teknologi Terapan, 2025)
Drought frequently occurs in Trenggalek Regency, with Prambon Village being one of the affected areas. The prolonged droughts in Prambon Village cause the water sources to dry up. As the population increases, so does the water demand. This study used arithmetic methods to project the population size until 2032. To assess the availability of water, the study used the F.J. Mock method and direct testing. According to the F.J. Mock method, the water balance indicated a surplus, projecting that the available water supply would meet the villagers' needs through 2032. However, the water balance based on data from the PKPLH Department and direct testing shows a deficit, insufficient to meet the population's needs until 2032. To address this issue, the conservation of water resources is necessary, involving the construction of spring protections, tree planting, and rainwater harvesting to ensure that the water needs of Prambon Village residents are met. This research serves as a reference for clean water utilization in Trenggalek Regency.